The Effect of Plant Growth Promoting Rhizobacteria Doses and NASA Liquid Organic Fertilizer on the Growth of Agarwood Seedlings - Hersi Martinsyah, Rachmad; Satria, Benni; Obel, Obel; Herawati, Netti; Erona, Meisilva (Jurnal Riset Perkebunan, 2025)
Agarwood (Aquilaria malaccensis Lamk.) is a highly sought-after non-timber forest product due to its valuable resin used in perfumes, medicines, and cosmetics. However, despite its significant commercial potential, agarwood cultivation in Indonesia remains underdeveloped, particularly in Sumatra. Agarwood seedling propagation can be achieved through land extensification, particularly by utilizing marginal lands. In West Sumatra, most marginal lands consist of ultisol soil, which has very low nutrient content. Therefore, the addition of organic matter and microorganisms is necessary to improve soil health and fertility to support plant growth. This study evaluated the effects of Plant Growth-Promoting Rhizobacteria (PGPR) and NASA Liquid Organic Fertilizer (LOF) on the growth of agarwood seedlings in ultisol soil, which is known for its low fertility and high acidity. The experiment employed a Completely Randomized Design (CRD) with two factors: PGPR (0, 10, 20, 30 ml/L) and NASA LOF (0, 20, 30, 40 ml/L). The results showed that the appropriate application of PGPR and NASA LOF significantly enhanced the growth and development of agarwood seedlings, highlighting their potential in improving agarwood cultivation on less productive ultisol soils. The best combination of PGPR and NASA LOF at a dose of 30 ml/L PGPR and 40 ml/L NASA LOF produced the highest average seedling height (82.34 cm) and the greatest number of leaves (38 leaves per seedling), with all seedlings surviving and meeting the quality standards for transplantation.